Tomato Role on Seven Deadliest Non-Communicable Disease - Lathifah Dzakiyyah Zulfa; Dessyani Salim; Abigail Tirza Melia Silalahi; Sharon Levita Hutapea; Margaretha Maria Odilia Natasha (Jurnal Indonesia Sosial Sains, 2021)
Non-communicable diseases such as ischemic heart disease, stroke, chronic obstructive pulmonary disease, lung cancer, Alzheimer, diabetes melitus, and kidney disease are leading causes of death in the world. There are many risk factors which can contribute to non communicable diseases such as dietary. Vegetable consumption such as tomato may lower risk factors to non-communicable diseases because of its active ingredient, lycopene, retinol, alpha tomatine, and tomatidine. In this review, authors aim to explain the mechanism of tomato’s active compound in lowering risk factors of non-communicable disease based on biomarker found on each disease collected from articles and journals. Lycopene and retinol have proven in reducing ischemic heart disease and stroke because of its antiatherogenic properties and anti-inflammatory effect. Antioxidative and anti-inflammatory effect of lycopene also proven in lowering risk factors of chronic obstructive pulmonary diseases by modulate reverse cholesterol transport, so cholesterol homeostasis is created. In lung cancer, lycopene and other bioactive compound such as α-tomatine and tomatidine also have an anti-proliferative effect by interacting with Epidermal growth factor receptor (EGFR). Its ability to reduce the final product of lipid peroxidation level makes lycopene lower Alzheimer risk factor. There is much more function of tomato’s active coumpound although pure tomato has contradictive effect on some disease.